Islamic Republic of Afghanistan : First Review Under the Under the Extended Credit Facility Arrangement and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Islamic Republic of Afghanistan. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2021)
Afghanistan is confronting the Covid-19 pandemic and its socioeconomic fallout amid rising insecurity. Supported by donors, the authorities boosted health and social spending to cushion the pandemic's impact on the vulnerable. Policy measures kept the output contraction to 2 percent in 2020, but poverty rose and the fiscal deficit widened. Political uncertainty has risen as the peace talks between the government and Taliban stalled and the U.S., NATO, and allies announced the withdrawal of their troops by September. In a strong sign of support for Afghanistan's development and reforms, donors pledged some USD 12 billion civilian grants over 2021-24 at the Geneva conference in November 2020.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Afghanistan, Islamic Republic of